Luandino Vieira's Short Fiction: Decolonization in the Third Register - Irwin Stern (Studies in 20th & 21st Century Literature, 1980)
The central theme of Luandino Vieira's short fiction is the «anthropological» daily existence in the musseques, slums, which surround the city of Luanda. The socio-political question of the epoch—the liberations movements and the repression by the colonial rulers—do not escape the author's view. Prior to the publication of Luandino's works, the language of Angolan fiction was indistinguishable from that of standard Portuguese fiction. The relationship of Quimbundo, the Bantu dialect of Luanda, and Portuguese is the key to the originality of Luandino's works. This becomes quite evident in the collections Velhas estórias and No amigamente na vida. Language register is Luandino's prime consideration. The «establishment» figures of the stories speak in Portuguese, while the people of the musseques function in Quimbundo. When the two social groups come into contact so do their languages. The result is a third register of speech, one which reflects the Portuguese-Quimbundo heritage and results in a new literary language. The basic contribution of Quimbundo is within the lexico-semantic area. In addition to a large number of Bantu words, new shades of meaning are given to common Portuguese terms through innovations in their traditional meaning and usage, as well as through their recreation along African language principles. Portuguese contributes its wealth of morphemes—principally suffixes—which enhance the Quimbundo vocabulary. Syntax is similarly recreated. Although Luandino's short fiction has been called hermetic, it does present an epoch of Angolan society. Its existence is an affirmation of national independence.
Keywords: Luandino Vieira; short fiction; anthropological; musseques; socio-political; epoch; liberations movement; colonialism; Angolan fiction; language; Portuguese; Angolan; Quimbundo; Bantu dialect; Velhas estórias; No amigamente na vida; literary language; lexico-semantic; hermetic; national independence